Function of gastrin-releasing peptide receptors in ocular itch transmission in the mouse trigeminal sensory system - Takanami, Keiko; Kuroiwa, Masaya; Ishikawa, Ren; Imai, Yuji; Oishi, Akane; Hashino, Midori; Shimoda, Yasushi; Sakamoto, Hirotaka; Koide, Tsuyoshi (Frontiers in Molecular Neuroscience, 2023)
The prevalence of allergic conjunctivitis in itchy eyes has increased constantly worldwide owing to environmental pollution. Currently, anti-allergic and antihistaminic eye drops are used; however, there are many unknown aspects about the neural circuits that transmit itchy eyes. We focused on the gastrin-releasing peptide (GRP) and GRP receptor (GRPR), which are reportedly involved in itch transmission in the spinal somatosensory system, to determine whether the GRP system is involved in itch neurotransmission of the eyes in the trigeminal sensory system. First, the instillation of itch mediators, such as histamine (His) and non-histaminergic itch mediator chloroquine (CQ), exhibited concentration-dependent high levels of eye scratching behavior, with a significant sex differences observed in the case of His. Histological analysis revealed that His and CQ significantly increased the neural activity of GRPR-expressing neurons in the caudal part of the spinal trigeminal nucleus of the medulla oblongata in GRPR transgenic mice. We administered a GRPR antagonist or bombesin-saporin to ablate GRPR-expressing neurons, followed by His or CQ instillation, and observed a decrease in CQ-induced eye-scratching behavior in the toxin experiments. Intracisternal administration of neuromedin C (NMC), a GRPR agonist, resulted in dose-dependent excessive facial scratching behavior, despite the absence of an itch stimulus on the face. To our knowledge, this is the first study to demonstrate that non-histaminergic itchy eyes were transmitted centrally via GRPR-expressing neurons in the trigeminal sensory system, and that NMC in the medulla oblongata evoked facial itching.